Investigation of temperature influence on photo-induced conductivity in n-type AlxGa1-xAs - Taquecita, Marco H. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Oliveira, L. [UNESP]; Li, M. Siu [UNESP]; Parreira, S. B. [UNESP] (Taylor & Francis, 1998)
We present conductance as function of temperature (G×T) under influence of monochromatic light in the range 0.5-1.5 μm for direct as well as indirect bandgap n-type AlxGa1-xAs. Results obtained below 60 K in indirect bandgap sample show the presence of another level of trapping, besides the DX centre, probably a X-valley effective mass state. In direct bandgap samples, these G×T curves show that above bandgap light increases conductivity to higher values than at room temperature and below bandgap light is not enough to avoid trapping. Photoconductivity spectra in indirect bandgap AlxGa1-xAs show that above ≅120 K, the absence of persistent photoconductivity contributes for a very clean spectrum. The mobility of AlxGa1-xAs is modelled considering dipole scattering. Data of transient decay of persistent photoconductivity is simulated using this approach.
Keywords: Computer simulation; Energy gap; Photoconductivity; Thermal effects; Thermoanalysis; Photo-induced conductivity; Semiconducting aluminum compounds